Моделювання та симуляція - Зуєва, А. Д. (ХНУРЕ, 2024)
In today's academic environment, modeling and simulation (M & S) play a critical role in learning and research for science and engineering students. A fundamental concept at M&S is simulation, which creates an approximation of the real world, and this is the first step in the process. This approach allows modification and improvement of models, ensuring repeatability of observations and analysis of systems in various aspects.